Ninth Five Year Plan (1997-2002) Proposal and Annual Plan 1997-98 Volume-II Government of Manipur - Planning Commission (Planning Commission, 1997)
Abstract of Financial outlay and expenditure for 8th Plan(1992-97) Annual Plan 1996-97; 9th Plan proposed outlays and Approved outlay for Annual Plan 1997-98 Ninth Plan (1997-2002) Proposed outlay and Approved outlay for Annual Plan 1997-98 GM Statement - II Progress of Expenditure during the 8th Plan (1992-97) Proposed outlay tor Ninth Plan (1997-2002) and Approver outlay for Annual Plan 1997-98 Physical Targets and Achievements during Eighth Plant (1992-97) Proposed for the Ninth Plant 1997-2002) and the Annual Plan 1997-98 Proposal for Spill-over and ongoing programmes/projects Proposals for Maximising benefits of completed programmed/projects Proposals for programmes/projects - New scheme of Ninth Plan, Summary Statement -Proposals for Programmes/Projects Statement regarding externally aided projects Draft Ninth Plan (1997-2002) and Annual Plan 1997-98 Outlays - By heads of Development - For district plans.
Government of Manipur, Planning Department